2018
DOI: 10.1186/s12888-018-1628-8
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of antidepressant medication use in individuals before and after being granted disability pension due to common mental disorders- a nationwide register-based study

Abstract: BackgroundEarly retirement caused by disability pension (DP) due to common mental disorders (CMDs) is frequent in European countries. Inadequate treatment, e.g., suboptimal antidepressant (AD) medication before DP can be crucial in such DP. This explorative study aimed to disentangle trajectories of AD based on defined daily dose (DDD) before and after granted DP, and to characterize the trajectories by socio-demographics and medical factors.MethodsAll 4642 individuals in Sweden aged 19–64 with incident DP due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…We observed a steep increase in the mean level of DDDs for psychotropic medications before disability retirement due to mental disorders both among those with high and low levels of pre-retirement ERI, which agrees with earlier findings. [2][3][4][5] Indeed, those with worsening mental health are likely to increase medication use, which is followed by admittance of disability pension and transition into disability retirement. This increase may also be explained by intensified treatment or rehabilitation activities when there is a threat of losing work ability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a steep increase in the mean level of DDDs for psychotropic medications before disability retirement due to mental disorders both among those with high and low levels of pre-retirement ERI, which agrees with earlier findings. [2][3][4][5] Indeed, those with worsening mental health are likely to increase medication use, which is followed by admittance of disability pension and transition into disability retirement. This increase may also be explained by intensified treatment or rehabilitation activities when there is a threat of losing work ability.…”
Section: Resultsmentioning
confidence: 99%
“…1 Previous studies have shown that a key indicator of mental disorders, namely psychotropic medication use, tends to increase before the transition to disability retirement followed by decrease after the transition, particularly if retirement was due to mental disorders. [2][3][4][5] Moreover, in some studies this decrease has been greater among people from a higher socioeconomic background, 3 suggesting that socioeconomic differences in workrelated exposures may modify changes in psychotropic medication use around the retirement period. Some studies from Asia found that mental health problems may increase after transition from work to non-work, 6 and voluntary 7 or non-voluntary retirement, 8 but at least in three European studies, retirement has been associated with a decrease in mental fatigue 9 and sleep disturbances 10,11 and an improvement in mental well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Similar methods have been used in previous studies to classify trajectories of annual antidepressant dose over time [35]. The authors of that study use latent class model, which is shown provide similar groupings to the sequence analysis used in the current study [36].…”
Section: Comparison With Existing Literaturementioning
confidence: 90%
“…The authors of that study use latent class model, which is shown provide similar groupings to the sequence analysis used in the current study [36]. The sample used in their study was very speci c -patients before and after being granted disability pension due to common mental disorders [35]. These individuals would have formed part of our 'out of labour force' group, which had the strongest relationship (OR 4.06; 95% CI 4.01 to 4.11) with having been prescribed most of the time and might explain why they found homogeneity in the pattern of the Daily De ned Dose (DDD) (i.e.…”
Section: Comparison With Existing Literaturementioning
confidence: 96%
“…On the other hand, previous studies on psychotropics consumption and disability pension process based on mental disorders are inconclusive. Rahman et al [14] found only little general temporal variation in antidepressant purchases among Swedish disability retirees with common mental disorders, but instead found multiple trajectory groups.…”
Section: Introductionmentioning
confidence: 99%